Oncological results in women with wound complications following mastectomy and immediate breast reconstruction: A meta‐analysis. Issue 5 (6th November 2022) - Cui, Wenting; Xie, Yiqun
Abstract: We performed a meta‐analysis to evaluate the oncological results in women with wound complications following mastectomy and immediate breast reconstruction. A systematic literature search up to August 2022 was performed and 1618 subjects with mastectomy and immediate breast reconstruction at the baseline of the studies; 443 of them were with wound complications, and 1175 were with no wound complications as a control. Odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CIs) were calculated to assess the oncological results in women with wound complications following mastectomy and immediate breast reconstruction using dichotomous or contentious methods with a random or fixed‐effect model. The wound complications had a significantly longer length of time to adjuvant therapy (MD, 9.44; 95% CI, 4.07–14.82, P  < .001) compared with no wound complications in subjects with mastectomy and immediate breast reconstruction. However, no significant difference was found between wound complications and no wound complications in subjects with mastectomy and immediate breast reconstruction in breast cancer recurrence (OR, 1.96; 95% CI, 0.95–4.06, P  = .07), death rates (OR, 1.95; 95% CI, 0.89–4.27, P  = .09), and kind of immediate breast reconstruction (OR, 1.01; 95% CI, 0.53–1.92, P  = .98). The wound complications had a significantly longer length of time to adjuvant, however, no significant difference was found in breast cancer recurrence, death rates, and kind of immediate breast reconstruction. The analysis of outcomes should be done with caution even though no low sample size was found in the meta‐analysis but a low number of studies was found in certain comparisons.